2020
DOI: 10.1016/j.surfcoat.2020.126460
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behavior of cold sprayed 7075Al composite coating reinforced with TiB2 nanoparticles

Abstract: Cold spray (CS), as a novel surface treatment technique, has been widely used for repairing damaged components and as protecting coatings, especially for the applications of aircraft and marine components. To further improve the mechanical properties, while maintaining the corrosion resistance of pure Al and Al alloy coatings, ceramic particles are commonly added into the Al matrix to produce particle-strengthened Al matrix composite (P-AMC) coatings. In this study, dense 7075Al composite coatings reinforced w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 70 publications
(79 reference statements)
0
11
0
Order By: Relevance
“…Electrochemical tests revealed that the TiB2/7075Al composite coating exhibited a higher corrosion rate than the pure 7075Al coating due to a galvanic coupling between TiB2 nanoparticles and the more active Al matrix. Therefore, the corrosion property of the CS AMCs was found closely connected to the porosity, microstructures, interactions between the Al matrix and the reinforcement particles, and the type of reinforcement particles [129].…”
Section: Corrosion Resistancementioning
confidence: 92%
See 1 more Smart Citation
“…Electrochemical tests revealed that the TiB2/7075Al composite coating exhibited a higher corrosion rate than the pure 7075Al coating due to a galvanic coupling between TiB2 nanoparticles and the more active Al matrix. Therefore, the corrosion property of the CS AMCs was found closely connected to the porosity, microstructures, interactions between the Al matrix and the reinforcement particles, and the type of reinforcement particles [129].…”
Section: Corrosion Resistancementioning
confidence: 92%
“…In general, SiC and Al2O3 particles are the two most commonly used reinforcements for anti-corrosion AMC coatings due to their neutral property. Xie et al [129] investigated the corrosion behavior of the cold sprayed TiB2/7075Al composite coating. Electrochemical tests revealed that the TiB2/7075Al composite coating exhibited a higher corrosion rate than the pure 7075Al coating due to a galvanic coupling between TiB2 nanoparticles and the more active Al matrix.…”
Section: Corrosion Resistancementioning
confidence: 99%
“…Hence, corrosion prevention for Mg alloy needs advanced and high-efficiency techniques. By depositing cold spray coating, the fatigue resistance can be enhanced’ [254], but in some cases cold spray coating does not have an effective enhancement in resistance against corrosion fatigue [251,255]. As per the research done by various authors on the corrosion of magnesium, the main corrosion type is pitting corrosion [256].…”
Section: Influence Of Processing Conditions On the Properties Of Cold...mentioning
confidence: 99%
“…There were no visible pores and cracks that penetrated the entire cross-section. Thus, it was not easy for a corrosive medium to directly infiltrate into the inner substrate [21,22]. In addition, a boundary between the repaired areas and the substrate was apparent.…”
Section: Microstructurementioning
confidence: 99%